New data on the Xantholinini from China. 28. New species from Yunnan, Sichuan and Hubei - Bordoni, Arnaldo (Contributions to Entomology = Beiträge zur Entomologie, 2017)
The following new species are described and illustrated for the listed countries: Mahavana vulcanicola spec. nov. (Yunnan) closely related to M. goaligong Bordoni, 2010; Megalinus yolounganus spec. nov. (Yunnan), related to M. hayashii Bordoni, 2002, and Atopolinus siping spec. nov. (Sichuan), closed to A. sinuatus Bordoni, 2013. Nomenclatural Acts Mahavana vulcanicola Bordoni – urn:lsid:zoobank.org:act:B2D2CDD6-2F9A-4B4C-B4BA-D5C2CDCC838B Megalinus yolounganus Bordoni – urn:lsid:zoobank.org:act:EB24FAF8-4AAB-4D02-A8D3-BF4AAAB687A6 Atopolinus siping Bordoni – urn:lsid:zoobank.org:act:8647C619-4AD2-41BE-B9B1-BD5246E9A520